PENENTUAN LOKASI AGROINDUSTRI KOPRA DI KABUPATEN MENTAWAI DENGAN SIMULASI SISTEM DINAMIK - Lisa Nesti, Irna Ekawati dan (Department of Agroindustrial Technology, Bogor Agricultural University, 2019)
Mentawai Islands Regency is an area in West Sumatra with its main commodity of copra. Copra produced by farmers is sold to several collectors and copra is carried outside the Mentawai for further processing by other parties. This research recommends the government to establish a copra-based agroindustry unit and bring greater added value to the Mentawai people. For this purpose, the establishment of an agro-industry consisting of copra processing plants and a major copra warehouse was proposed. This main warehouse supplyis derived from warehouses that exist on every major island in the Mentawai Islands regency. Copra produced by farmers will be directly purchased and stored in copra warehouses on each island and then sent to the main warehouse and then subsequentlyprocessed at the copra processing plant. The proposal to determine the location of the agro-industry was decided by considering the logistical costs incurred for the delivery of raw materials to the main warehouse along the copra supply chain flow which included the cost of savings and shipping costs. Location selection was carried out with a dynamic system approach due complex inter-island supply systems with copra supply values depend on the time function. Dynamic system simulation was carried out with three scenarios of agroindustry locations, namely Siberut, South Sipora, and Sikakap Island. Simulation results showed that the establishment of the main factory and warehouse was established on Sipora Island because it generates the lowest total logistics costs.Keywords: location determination, copra, mentawai, simulation, logistic